Особенности распыления кремниевых и углеродных мишеней ускоренными ионами фуллерена C₆₀ - Малеев, М. В.; Зубарев, Евгений Николаевич; Пуха, Владимир Егорович; Дроздов, Антон Николаевич; Вус, А. С.; Девизенко, Александр Юрьевич (Харківський національний університет ім. В. Н. Каразіна, 2015)
В работе исследованы закономерности роста пленок и эрозии поверхности при облучении мишеней из углерода и кремния пучком ускоренных ионов C₆₀ с энергией в интервале 2,5-24 кэВ при температуре мишеней 373 K. Установлено, что рост углеродных пленок на поверхности облучаемых кремниевых мишеней наблюдается до энергий ионов 7 кэВ, а на поверхности углерода до 19 кэВ. При энергии ионов выше указанных значений пленка на поверхности не формируется и наблюдается эрозия материала мишеней. Исследованы структура и механические свойства углеродных пленок, выращенных в интервале энергий ионов фуллерена 2,5-11,5 кэВ.

We studied patterns of film growth and surface erosion during irradiation of carbon and silicon beam of accelerated ions with energies of C₆₀ in the range of 2,5-24 keV at a temperature of 373 K. targets established that the growth of carbon films on the surface of the irradiated silicon target is observed to energies 7 keV ions and at 19 to the surface of carbon keV. When the ion energy above the specified values on the surface of the film is not formed and there is erosion of the target material. The structure and mechanical properties of carbon films grown in the range of ion energies fullerene 2,5-11,5 keV. Keywords: carbon, silicon, fullerene, erosion, sputtering, ion accelerated C₆₀, film structure.
The features of sputtering silicon and carbon targets with accelerated fullerene C₆₀ ions
Keywords: углерод; кремний; фуллерен; эрозия; структура пленок; carbon; silicon; fullerene; erosion; film structure